Molecular and chemical markers to illustrate the complex diversity of the genus Lupinus (Fabaceae) - Bermúdez Torres, Kalina; Ferval, Maxime; Hernández-Sánchez, Arianna Michelle; Tei, Andreas; Gers, Charles; Wink, Michael; Legal, Luc (Diversity, 2021)
The potential of secondary metabolites as systematic markers to get new insights in an intricate phylogeny of a recent evolutionary radiation is explored. A chemosystematic study of the genus Lupinus (Fabaceae) was performed, using quinolizidine (QA) and piperidine alkaloids (ammodendrine) as diagnostic characters. Seven major QA and the piperidine alkaloid ammodendrine were found to be the most frequent compounds. Two groups were supported according to their geographic origin: an Old World/Atlantic American group and a West New World group and this pattern is concordant with molecular data (here, based on an original barcode approach using the nuclear marker ITS). However, QA profiles are less informative at the species level. Despite a lack of resolution within the two groups, the alkaloid profiles agree with well supported clades based on DNA molecular characters. The combined use of chemical and barcode genetic markers represents a viable alternative for separating recent evolutionary lineages to a first approximation without having to resort to an expensive and sophisticated molecular arsenal such as next generation sequencing.
Gesehen am 12.08.2021